The Role of Word of Mouth (WOM) in Building Consumer Trust in New Brands: Strategy Analysis and Impact - Umroatus Soleha; Farrah Noor Aminah Ilfah; Ahmad Hasinul Adabi; Muhammad Alkirom Wildan (Badan Penerbit STIEPARI Press, 2025)
This research examines the role of Word of Mouth (WOM) in building consumer trust in new brands and the strategies that can be applied to make WOM more effective. In an increasingly competitive business world, WOM, both in conventional and digital forms (electronic Word of Mouth/e-WOM), has become one of the main factors that influence brand image and consumer purchasing decisions. This study explores how WOM can enhance the credibility of a new brand through customer recommendations, online reviews, and interactions that occur on various social media platforms. Through literature analysis and theoretical studies, this study found that WOM has a significant influence on shaping consumer perceptions of a new brand. Some of the factors that play a role in the effectiveness of WOM include the level of trust in the source of information, the frequency of conversations about the brand, and the media used in disseminating information. In addition, the utilization of digital marketing strategies that integrate social media with active consumer involvement can further strengthen the impact of WOM in building customer trust and loyalty to a new brand. With these findings, businesses are expected to maximize WOM as an effective marketing strategy to improve the competitiveness and positioning of new brands in the market.